Analisis Muatan Literasi Statistik Pada Buku Teks Matematika Di Platform Merdeka Mengajar Jenjang Sekolah Dasar - Prasetyo, Rudi; Muksar, Makbul; Rufiana, Intan Sari (Universitas Nahdlatul Ulama Blitar, 2025)
This study aims to determine the content of statistical literacy in the independent curriculum textbooks found on the Merdeka Teaching Platform (PMM). This research was conducted using a qualitative descriptive method, namely by describing the information obtained in non-numerical form. The data collection process is carried out using content analysis, which is a systematic and in-depth examination of the content of a particular material in order to identify patterns, themes, and biases. The textbooks selected in this study consisted of 4 textbooks, 1 grade I textbook, 2 grade IV textbooks and 1 grade V textbook. The analysis of statistical literacy content in Mathematics textbooks at the PMM elementary school level is carried out on 4 books that have presented statistical literacy content according to the applicable curriculum. The cognitive level of statistical literacy skills presented in the book includes understanding, application, evaluation and reasoning.